Efektivitas Pemberian Pupuk Organik Cair (POC) dari Urin Sapi terhadap Pertumbuhan Tanaman Selada (Lactuca sativa L.) - Rahmawati, Fitri; Efendi, Ismail; Masiah, Masiah (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
The purpose of this study was to test and determine the concentration of Liquid Organic Fertilizer (LOF) from cow urine that is most effective for the growth of Lettuce (Lactuca sativa L.) plants. This type of research is experimental research. The research approach used is quantitative and qualitative. The research design used is Completely Randomized Design (CRD). The population in this study were all lettuce seedlings that had been sown. The sample used in this study was lettuce plants totaling 30 seedlings. The parameters observed were plant height and number of leaves of Lettuce (Lactuca sativa L.) plants. Furthermore, the data analysis used was one way ANOVA with the SPSS 21 for Windows program. The results of the study showed that the best dose of Liquid Organic Fertilizer (LOF) from cow urine was in the treatment of P2: 200 ml of POC from cow urine + 800 ml of water, which was to produce the highest plant height of 7.59 cm, and the treatment of P1: 100 ml of POC from cow urine + 900 ml of water produced the highest number of leaves, which was 5.30 strands.